(untitled) (Challenges of the Future, 2021)
Purpose and Originality: The aim of the article was to analyse the work of the health policy which is a very specific part of social policy. In the work we focus on its financing, which is a very important issue in the health care. We try to show, what is the role of the state in the health care system as well as the creation of resources and control costs in the health sector. The work is finding such as financing health care in Slovakia and in other selected countries, and which could be changed for the best operation. Method: The analysis was carried out on the basis of the information which I drew from books and Internet resources. The work is divided into two parts. Contains 9 tables and 3 charts. The first chapter is devoted to a general description of social policy, its funding, with a focus on health policy than its specific area. The second chapter analyses the financing systems of health policy in Slovakia and in selected countries. Results: The results showed that the Slovak health care makes is trying hard to catch up with the level of the best health care systems. However, there are countries, which are doing much worse than us, in terms of funding. Society: It is important to properly invest money but also communication between states. To get help on health and to ensure that citizens know states the best conditions of health care. Limitations / further research: This work is focused on how to bring closer health care and its financing in several different countries economically. IN doing so some other aspects such as what is best level of services, etc. were put aside.